PELAKSANAAN FUNGSI-FUNGSI DPRD: STUDI KASUS DI DPRD KOTA BOGOR PERIODE 1999-2004 - Aisyah, Siti (LPPM Universitas Terbuka, 2006)
As the house of representative at the local level, the Local Legislative (Dewan Perwakilan Rakyat Daerah/DPRD) plays three key functions, they are legislation, budgeting and controlling. In then conducting those functions, DPRD had a role of being a channel for public aspiration. The study analyzed the implementation functions of the DPRD in the 1999-2004 periods in Bogor, West Java.  This research discusses the implementation of legislative, budgeting and political controlling functions in the Bogor Local Legislative (DPRD kota Bogor).  It is aimed to review political representative at the local level, specially the implementation of DPRD functions as a channel for public aspiration.  Therefore, it is expected to be useful as an evaluation and recommendation for DPRD to play role as a channel for public aspiration.